Systems Engineering and Safety Issues in Scientific Facilities Subject to Ionizing Radiations. (24th October 2013) - Bonnal, Pierre; Baudin, Mathieu O.; Ruiz, Jean-Michel
The conception and development of large-scale scientific facilities emitting ionizing radiations rely more on project management practices in use in the process industry than on systems engineering practices. This paper aims to highlight possible reasons for this present situation and to propose some ways to enhance systems engineering so that the specific radiation safety requirements are considered and integrated in the approach. To do so, we have reviewed lessons learned from the management of large-scale scientific projects and more specifically that of the Large Hadron Collider project at CERN. It is shown that project management and systems engineering practices are complementary and can beneficially be assembled in an integrated and lean managerial framework that grants the appropriate amount of focus to safety and radiation safety aspects.